MANAJEMEN BERBASIS MADRASAH DALAM PENINGKATAN MUTU DI MTsN WATAMPONE KABUPATEN BONE - FAJRI DWIYAMA (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstract: This study aims to provide an overview of madrasah-based management in Madrasah Tsanawiyah Negeri 1 Watampone, and madrasah-based management in improving the quality of Madrasah Tsanawiyah Negeri 1 Watampone. This research is a type of qualitative research. The source of the research data was the head of the madrasah, the deputy head of the madrasah curriculum section, the deputy head of the madrasah in the infrastructure facility, the deputy head of the madrasah in the student section, the deputy head of the madrasah in the public relations department, the teacher, and the school committee. Data collection techniques used are observation, interviews, and documentation. The collected data is analyzed through steps of data reduction, data presentation, and data verification. The results of the study found that madrasah-based management in Madrasah Tsanawiyah Negeri 1 Watampone has been carried out well, through planning stages with the preparation of work programs and budget plans involving all madrasa components. The implementation of the work program is carried out according to each division of labor. Madrasa leadership is carried out by the head of the madrasah. Supervision and evaluation are carried out to ensure that all activities are carried out properly and as a reference for further improvements. Madrasah information systems are used to obtain information on the development of education. Quality improvement in Madrasah Tsanawiyah Negeri 1 Watampone is carried out by meeting all national standards of education criteria and improving student achievement. In fulfilling the criteria for standard nasinonal education, it is ensured by carrying out all activities related to this matter through the leadership of a strong madrasa head, good cooperation between madrasah components, and fulfillment of professional duties and responsibilities. Kata Kunci: Management, Quality, Madrasah